Transformasi Metode Tafsir Maudu’i: dari Mufasir Klasik Hingga Mufasir Kontemporer - Abubakar, Achmad; Yusuf, Muhammad; Rifah, Afwaz Fafaza (Shautuna: Jurnal Ilmiah Mahasiswa Perbandingan Mazhab, 2024)
The Maudu'i interpretation method was born from various factors, including as a form of development of existing interpretation in accordance with current developments which require the birth of new methods and does not rule out the demands of the times and the development of science in seeing phenomena that appear in society. The research used in this case is library research. The data collected emphasizes books, journals, articles and other literature that are related to the main research problem, then reviewed in more depth and concluded. The results of this research show how important the Maudu'i interpretation method is in answering problems among the community and making it easier for the community to look at the various views of interpreters from classical to contemporary times who have their own characteristics in developing the Maudu'i interpretation method, this is to avoid It is assumed that every exegete has had disagreements in applying the steps of the Maudu'i exegesis method, which of course is still relevant today.